Authoritarian Parenting in Muslim Family Education: An Analysis of Attachment Theory and Mu‘āsyarah bil Ma‘rūf - Novita Rahmadani; Wahidatul Mustaqimah; Mutia Rani Alghozali; Kunhaniah Mabruroh (ZHAFIRO: Journal of Islamic Education and Social, 2026)
This study aims to analyze the characteristics of authoritarian parenting in Muslim family education, its impact on children's attachment formation based on Attachment Theory, and its relevance to the principle of Mu'asyarah bil Ma'ruf. This research employed a qualitative approach using a library research method. Data were collected from various books, scholarly journal articles, and relevant academic literature and were analyzed through content analysis. The findings indicate that authoritarian parenting is characterized by dominant parental control, one-way communication, and a strong emphasis on children's obedience. Such parenting practices may hinder the development of secure attachment due to limited responsiveness to children's emotional needs. From the perspective of Mu'asyarah bil Ma'ruf, authoritarian parenting is less consistent with the principles of compassion, respect, justice, and constructive communication within the family. This study highlights the importance of developing parenting practices that integrate firmness, affection, dialogue, and emotional engagement to support a more humane and sustainable model of Muslim family education.